A case study of argument diagramming in Thai and Indonesian higher education argumentative essays - Annisa Laura Maretha; Intan Pradita (Universitas Syiah Kuala, 2024)
This study explores first-year undergraduate students argumentation essays using argument diagramming structure. A corpus-driven data of 394 argumentative essays were gathered from both Indonesian and Thai universities. A content analysis was employed to examine the dataset of the students argumentative essays. After gathering primary information from the body parts of their essays, we subcategorized their argumentations into claims and premises in a compliant reading. To ensure data trustworthiness, this study employed triangulation by source and method. The findings show that the most prominent type of argument diagramming was a basic argument, followed by convergent and divergent arguments. Regardless of how the argument diagramming was written, the study found that the students still lacked mastery in structuring their logic when building up the case to be extended to claims and premises. This study suggests a need to revisit pedagogical instructions, in which there should be a provision not only on the basic knowledge of argument structures but also on the skills to recognize the quality of a good argument cognitively. This additional practice will provide important insights to recognize the representational strengths and weaknesses of the students argumentative writing proficiency to achieve a better performance in the content of their essays.